Biogas (IntechOpen, 2023)
Anaerobic digestion (AD) is by far the most important technology for providing clean renewable energy to millions in rural areas of many developing countries. AD of biowastes produces both biomethane and anaerobic digestate as a byproduct that can be used further as a biofertilizer. Biowastes including sewage, food processing wastes, animal wastes, and lignocellulosic wastes typically produce biogas containing 55%–70% biomethane. In the context of energy consumption, more than 85% of the total energy consumed currently comes from non-renewable fossil resources. Biogas technology can provide sustainable, affordable, and eco-friendly energy through waste recycling. This book provides basic knowledge and recent research on biogas production, focusing on the enhancement of biomethane and production routes integrated with microalgae cultivation or agriculture.